Ketamine Infusion as a Single Sedative Agent for Post-Intubation Management of Critically Ill Patients: A Systematic Review and Meta-Analysis - Maghraby, Nisreen; Ahmed Almulihi, Qasem; Nemeth, Joe; Alghanim, Mohammed Hajay; Barbic, David; Al Rajeh, Ibrahim Khalil; Haji, Arwaa Khalid M (Archives of Academic Emergency Medicine, 2025)
Introduction: Combining multiple drugs for intubation raises concerns such as increased side effects, medication errors, nursing workload, and costs. Ketamine, with its anesthetic and analgesic properties, shows promise as a sedative agent for post-intubation care. This study aimed to evaluate the efficacy and safety of ketamine infusion as the sole sedative for critically ill intubated patients. Methods: Following PRISMA 2020 guidelines, we conducted a systematic review by searching Ovid MEDLINE, Cochrane Central Register of Controlled Trials, and Google Scholar up to May 10, 2024. We included studies assessing ketamine use for post-intubation sedation in critically ill adults or children. Study quality was assessed using the Newcastle–Ottawa scale, and meta-analysis was performed using a random-effects model. Results: The systematic review included 7 studies, with 4 studies included in the meta-analysis. There was no significant difference in mortality (OR = 1.52; 95% CI: 0.49–4.70, p = 0.46; I2 = 83%) or length of hospital stay (MD = 6.42; 95% CI: -1.42-14.26, p = 0.11; I2 = 84%) between the ketamine only and other groups. The most common adverse events in the ketamine infusion group were atrial fibrillation and agitation. Conclusion: Single-agent ketamine infusion is effective and safe for critically ill intubated patients. No significant differences were found in mortality or hospital stay between ketamine only and other groups. Atrial fibrillation and agitation were the most common adverse effects.